THE NEED TO INTRODUCE COMPUTERIZED MEDICAL TRIAGE SCALES - Bakhrom E. Yuldashev; Noiba T. Yuldasheva (Central Asian Journal of Medicine, 2025)
The article discusses the importance of introducing computerized medical triage scales (CMTS) into modern healthcare systems. Their advantages over traditional triage methods, impact on diagnostic speed and resource allocation in emergency departments (EDs) are analyzed. Particular attention is paid to the algorithms CAP-SORT, TS, RTS, CRAMS, SORT and MEES. Data on the impact of automated triage on mortality, waiting time and clinical outcomes are presented.